Effects of atrazine on tissue damage, physiological and biochemical changes and transcriptome in marine medaka (Oryzias melastigma) - Kaikai Liu; Meili Xin; Qian Liu; Tong Liu; Daode Yu; Xianlei Wang; Zhipeng Zhang; Jian Zhou; Wendan Chi; Mengxue Xu; Haiyi Wu; Jingjing Song (Aquatic Toxicology, 2026)

Effects of the nervonic acid-rich microalga Mychonastes afer on the growth and reproductive processes of Oryzias melastigma - Lu Sun; Kaikai Liu; Xiaoyi Shi; Xia Fang; Daode Yu; Yongjiang Xu; Hui Wang; Jingjing Song; Yong Fan; Fuli Li (Algal Research, 2025)

Reef effect of vertical relief on the shelter-seeking and foraging processes of juvenile fat greenling (Hexagrammos otakii) in a mesocosm experiment - Yue Zhang; Tao Sun; Gang Ding; Bo Li; Shuhan Li; Wei Yang; Daode Yu; Xiaoling Wang; Qianzhao Sun; Haiying Lin (Applied Animal Behaviour Science, 2024)

Exposure to manganese (II) chloride induces developmental toxicity, oxidative stress and inflammatory response in Marine medaka (Oryzias melastigma) embryos - Kaikai Liu; Daode Yu; Meili Xin; Fang Lü; Zhipeng Zhang; Jian Zhou; Tong Liu; Xiaohui Liu; Jingjing Song; Haiyi Wu (Aquatic Toxicology, 2023)

Moderate relative size of covered and non-covered structures of artificial reef enhances the sheltering effect on reef fish - Yue Zhang; Tao Sun; Gang Ding; Daode Yu; Wei Yang; Qianzhao Sun; Xiaoling Wang; Haiying Lin (Frontiers in Marine Science, 2023)
Identifying the relationship between fish aggregations and artificial reefs (ARs) is important for optimizing reef structures and protecting marine resources subjected to external disturbance. Yet, knowledge remains limited of how the distribution of fish is affected by shelter availability provided by different AR structures. Here, we tested the effects of two structural attributes on the distribution of a benthic juvenile reef fish (fat greenling, Hexagrammos otakii ). We used a laboratory mesocosm experiment with a simplified reef unit that was made of covered structure and non-covered structure. The covered structure was defined as the area inside ARs that provided effective shelter. The non-covered structure was defined as the area along the edge of ARs, which attracts fish but has lower sheltering effects. Four scenarios of two orthogonal structural attributes contained in a reef unit were implemented: size of covered structure (small shelter versus large shelter) and size of non-covered structure (small edge versus large edge), forming three size ratios of shelters to edges (low, medium, and high). The sheltering effects of the four scenarios were evaluated based on changes to the distribution patterns of fish under disturbance. We found that the reef with a large shelter had a better sheltering effect than the reef with a small shelter, but was limited by its small edge, especially when fish density was high. In contrast, the sheltering effect of the reef with a small shelter was limited by its large edge compared to the small edge. Thus, a moderate shelter-edge ratio enhanced the ability of juvenile fat greenling to elude external disturbance. Our findings highlight the importance of quantifying how the structural composition of reefs affects fish distributions, providing guidance to optimize AR structures.

Reduced salinity interacts with ultraviolet radiation to alter photosystem II function in diatom Skeletonema costatum - Shasha Zang; Fang Yan; Daode Yu; Jingjing Song; Lei Wang; Zhiguang Xu; Hongyan Wu (Journal of Oceanology and Limnology, 2022)

Antimicrobial Defensin and DNA Traps in Manila Clam Ruditapes philippinarum: Implications for Their Roles in Immune Responses - Yijing Han; Gege Hu; Yuying Chen; Lizhu Chen; Daode Yu; Qianqian Zhang; Dinglong Yang (Frontiers in Marine Science, 2021)
Although defensins have been isolated from a variety of metazoan, their role in cellular immunity has not been answered. In the study, we found that the hemocytes of the Manila clams Ruditapes philippinarum release defensin (designated as Rpdef3) in response to Vibrio parahaemolyticus challenge. The antimicrobial Rpdef3 was proved to be involved in the extracellular traps (ETs) that hemocytes released in response to Vibrio challenge. Scanning electron microscopy observation proved the patterns how ETs eliminate invading bacteria. Furthermore, Rpdef3 involved in ETs had broad-spectrum antimicrobial effect on both Gram-negative bacteria and Gram-positive bacteria. ELISA assay revealed that Rpdef3 could bind lipopolysaccharides and peptidoglycan in a dose-dependent manner. As concerned to the antibacterial mechanisms, Rpdef3 can cause bacterial membrane permeabilization, leading to cell death. As a result, Rpdef3 might contribute to the trap and the elimination of invading Vibrio in clam ETs. Taken together, our study suggest that the formation of ETs is a defense mechanism triggered by bacterial stimulation, coupled with antibacterial defensin.

Observation and analysis of morphology abnormalities in development of Oryzias melastigma embryos - Jingjing Song; Haiyi Wu; Kaikai Liu; Wendan Chi; Shanshan Ge; Zhipeng Zhang; Mingqi Wang; Yi Yu; Daode Yu (Journal of Oceanology and Limnology, 2021)